Creating a Digital 3D Model of the Dental Cast Using Structure-from-Motion Photogrammetry Technique - Al-Tameemi, Reem; Hamandi, Sadiq; Al-Mahdi , Akmam (International Journal of Online and Biomedical Engineering (iJOE), 2023)
Photogrammetry is a technique used to obtain a reliable database of any physical object, by creating a digital 3d model using multiple photos taken at different angles around the object. Recently, several fields have used this technique to build digital 3D models, such as topography, architecture, engineering, and medicine. Many recent dentistry studies have used the Structure-from-motion (SfM) Photogrammetry technique to reconstruct a digital three-dimensional (3D) model of a dental cast as an alternative to conventional scanning. In this research, the dental casts are constructed by applying the SfM Photogrammetry technique in which a guide to stepwise workflow is provided by utilizing simple tools which are: a smartphone camera, homemade photo studio setup, and Agisoft Metashape software. The agreements between the generated models and the reference dental casts are assessed using the Bland Altman method by calculating the mean value differences. All the calculated differences are not statistically significant (P-value >0.05), and they are also clinically accepted as the range of the mean differences (-0.042 to 0.355) is less than 0.5mm. this demonstrates that the resulted 3D models closely approximate the overall geometry of the dental casts.